2012
DOI: 10.1002/jcc.23061
|View full text |Cite
|
Sign up to set email alerts
|

The role of the basis set and the level of quantum mechanical theory in the prediction of the structure and reactivity of cisplatin

Abstract: In this article, we conducted an extensive ab initio study on the importance of the level of theory and the basis set for theoretical predictions of the structure and reactivity of cisplatin [cis‐diamminedichloroplatinum(II) (cDDP)]. Initially, the role of the basis set for the Pt atom was assessed using 24 different basis sets, including three all‐electron basis sets (ABS). In addition, a modified all‐electron double zeta polarized basis set (mDZP) was proposed by adding a set of diffuse d functions onto the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…In order to further improve the representation of this type of Pd(II)-amine complex, it is of paramount importance to develop new basis sets as recently undertaken for Pt(II) complexes 19,42 (which was beyond the scope of this work). At the moment, it seems that the precise estimate of one type of metal-ligand bond length leads to uncertainty in the other one, and an improvement of the bond lengths results in a worse description of the bond angles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to further improve the representation of this type of Pd(II)-amine complex, it is of paramount importance to develop new basis sets as recently undertaken for Pt(II) complexes 19,42 (which was beyond the scope of this work). At the moment, it seems that the precise estimate of one type of metal-ligand bond length leads to uncertainty in the other one, and an improvement of the bond lengths results in a worse description of the bond angles.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, quantum mechanical calculations were carried out for Pd 2 -Spm at the DFT level, since this approach has been shown to deliver accurate results for this type of system. [17][18][19] A theoretical model previously reported by the authors for a mononuclear Pd(II) compound bearing non-chelating ligands 17 was presently evaluated because of its suitability for the highly flexible polynuclear polydentate chelate Pd 2 -Spm. The accuracy of the calculated results was assessed by comparison with the experimental data available on this chelate -both studies reported X-ray structural information 14 and the vibrational results gathered in this work.…”
Section: Introductionmentioning
confidence: 99%
“…The geometries for the cis and trans isomers were optimized in the gas phase at the B3LYP level [24] with the 6-31+G(d) basis set used for hydrogen and heavy elements, except for the metal for which the LanL2DZ [25] effective core potential was set for core electrons with its balanced double-zeta basis set for valence electrons [26]. This calculation scheme is abbreviated as B3LYP/LanL2DZ/6-31+G(d) and was recently evaluated for cisplatin reactivity [27]. The same level of theory was used for vibrational frequency calculation in order to characterize the structures as true minima on the potential energy surface (all harmonic frequencies real) as well as to analyze the vibrational normal modes.…”
Section: Calculationsmentioning
confidence: 99%
“…2. In order to assess most of DFT approaches and basis sets to predict hydrolysis energy barrier for Pt(II) complexes, please refer to the reference [34]. The transition states (TS) were assembled for all conformations aiming to assess the conformational role on the reaction rate.…”
Section: Theoretical Methodologymentioning
confidence: 99%